Analysis of the development of social branding in the Republic of Kazakhstan (Вестник КазНУ. Серия Экономическая, 2016)
Knowledge of essence of processes of social branding, effective technologies of creation and development of social brands is relevant today both for each organization of the social sphere, and for the organization working in the sphere of the economy but thus realizing importance of the social responsibility and actively participating in implementation of social programs. Social branding has the specifics which don’t allow to build sociocultural brands on the basis of the marketing strategy wide spread in branding of goods and services of mass consumption. There by in this article features of social – oriented branding are revealed and the development of a brand in the social sphere of the Republic of Kazakhstan is considered . In article the analysis of museum activity of Kazakhstan is provided and problems of development of a brand of the museums in the city of Almaty are revealed. In the result, solutions of the revealed prob lems were offered . And also in the article practices of foreign countries on studying and using the principles and methods of creation of a social brand of the museum, recommendations for creation of a social brand of the Central State museum of the city of Almaty are considered.